2018
DOI: 10.1002/joc.5746
|View full text |Cite
|
Sign up to set email alerts
|

Northeast United States growing season moisture conditions: Associations with a North American mid‐tropospheric wave train

Abstract: The Palmer Drought Severity Index is examined in the Northeast United States during the May–September growing seasons of 1950–2016, seeking to better understand the role of atmospheric circulation in moisture variability. Moist conditions for the Northeast are associated with the development of a mid‐tropospheric wave train over the United States, with enhanced ridging over the west, a trough over the Ohio Valley, and ridging over the Atlantic Ocean east of Newfoundland that favours enhanced uplift, precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…At many wells, the May NAO was negatively correlated with groundwater recharge in both current RY and subsequent fall recharge seasons, indicating that a negative phase of the NAO would lead to increased groundwater recharge (Figures 3 and 5). Previous literature has found that negative NAO conditions are associated with meridional flow, increased blocking, colder temperatures, and an eastward displaced trough axis which would allow coastal storms to track almost directly east away from the Atlantic coast, contributing to reduced precipitation totals across the Northeast (Archambault et al, 2008; Bradbury, Dingman, et al, 2002; Bradbury, Keim, et al, 2002; Shabbar et al, 2001; Suriano et al, 2018; Yarnal & Leathers, 1988). The negative correlation found between RY and fall recharge with May's NAO index does not support findings in previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At many wells, the May NAO was negatively correlated with groundwater recharge in both current RY and subsequent fall recharge seasons, indicating that a negative phase of the NAO would lead to increased groundwater recharge (Figures 3 and 5). Previous literature has found that negative NAO conditions are associated with meridional flow, increased blocking, colder temperatures, and an eastward displaced trough axis which would allow coastal storms to track almost directly east away from the Atlantic coast, contributing to reduced precipitation totals across the Northeast (Archambault et al, 2008; Bradbury, Dingman, et al, 2002; Bradbury, Keim, et al, 2002; Shabbar et al, 2001; Suriano et al, 2018; Yarnal & Leathers, 1988). The negative correlation found between RY and fall recharge with May's NAO index does not support findings in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…This result is despite the potential importance of summer air temperature to summer/fall minimum flows through evapotranspiration. Additionally, studies that considered meteorological drivers of drought conditions across the Northeast have found that precipitation was a much stronger control on drought conditions than temperature or evapotranspiration (Ficklin et al, 2015; Leathers et al, 2000; Suriano et al, 2018). The effects of climate change could reduce groundwater recharge if increases in temperature and evapotranspiration exceed expected increases in precipitation in NNE (Bjerklie et al, 2011), but based on the historical data used in our study, groundwater recharge to date is strongly related to precipitation and not temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all cases, synoptic classification efficiently isolates similarly occurring atmospheric conditions as individual synoptic weather types, aiding researchers in determining the impact each weather type has on the topic of interest (Yarnal, 1993). These techniques are also advantageous in their ability to serve as a method to connect scales, linking global‐scale processes to local‐scale phenomena (Suriano et al., 2018). Connecting scales allow for a pathway of physical forcing mechanisms to be established, furthering the scientific understanding of the climate system.…”
Section: Introductionmentioning
confidence: 99%